2019
DOI: 10.18488/journal.1.2019.92.248.255
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Occupational Stress on the Management of an Organization

Abstract: Occupational stress is an important issue not only for the researchers but also for the employees and managers at work. This study aims to determine the effects of occupational stress on job satisfaction, intention to leave and absenteeism. A sample of 100 employees in the Companies Commission of Malaysia, a statutory body regulating companies and businesses was recruited to participate in the study. A questionnaire was used to collect information on demographics, stress, job satisfaction, intention to leave a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 18 publications
0
5
2
Order By: Relevance
“…OS was examined and retained a significant positive association with turnover intention, and the results indicate an increasing chance of leaving the organization because of increased stress to employees (Husain et al, 2015). This result contradicts with findings of Wen et al (2020) as they reported that stress does not motivate employees to resign their job immediately and the findings of Yahaya et al (2019) in which they found no direct significant relationship between occupational stress and turnover intention in the different economies than Nepal. These This study revealed a significant relationship between service climate and occupational stress, declaring positive service climate causes to decrease occupational stress.…”
Section: Discussioncontrasting
confidence: 82%
See 4 more Smart Citations
“…OS was examined and retained a significant positive association with turnover intention, and the results indicate an increasing chance of leaving the organization because of increased stress to employees (Husain et al, 2015). This result contradicts with findings of Wen et al (2020) as they reported that stress does not motivate employees to resign their job immediately and the findings of Yahaya et al (2019) in which they found no direct significant relationship between occupational stress and turnover intention in the different economies than Nepal. These This study revealed a significant relationship between service climate and occupational stress, declaring positive service climate causes to decrease occupational stress.…”
Section: Discussioncontrasting
confidence: 82%
“…Organizations with high turnover rates have a direct loss of their business as they transfer their competencies and business ideas to other organizations. Employee turnover intention has a significant relationship with job satisfaction (Mwesigwa et al, 2020), job security (Ghandi et al, 2017;Chung et al, 2017), role ambiguity (Wen et al, 2020;Erera-Weatherley, 1996), WL (Wen et al, 2020), occupational stress (Yahaya et al, 2019) and growth opportunity (Busari et al, 2017). These research findings indicate that prior studies were focused on identification of occupation stress and their impact on workplace paying less attention on the relationship of serial mediation.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations